Phyllogomphoides enriquei (Odonata: Gomphidae) a new species from Mexico - Torres-Pachón, Mónica; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2017)
Phyllogomphoides Belle, 1970, is the second most diverse genus with 46 species within neotropical Gomphidae, after Progomphus Selys, 1854 with 69 species. Most of the Mexican species are very similar in color pattern, however, the male accessory genitalia, cerci and epiproct allow to identify and separate species. Here, Phyllogomphoides enriquei sp. nov. (holotype ♂: Mexico, Michoacán, Municipality of Tepalcatepec, Río Pinolapa, 19º00.524 N; 103º01.456 W, elevation 616m, 04 July 2005, R. Novelo & J.A. Gómez leg.; to be deposited in Colección Entomológica del Instituto de Ecología, A.C., Xalapa) is described and illustrated, being characterized by the anterior hamuli bilobed, tumid anteriorly, ending in a strong spine posteriorly, followed by a wide, deep cleft between anterior and posterior lobes. It appears to be closely related to Phyllogomphoides luisi González-Soriano & Novelo-Gutiérrez, 1990. A distributional map of Phyllogomphoides species from Michoacan State is provided. With this discovery, the number of species of Phyllogomphoides for Mexico rises to 13.